Genetic structure of pharmacogenetic biomarkers in Brazil inferred from a systematic review and population-based cohorts: a RIBEF/EPIGEN-Brazil initiative. Issue 6 (December 2018) - Rodrigues-Soares, Fernanda; Kehdy, Fernanda; Sampaio-Coelho, Julia; Andrade, Poliana; Céspedes-Garro, Carolina; Zolini, Camila; Aquino, Marla; Barreto, Mauricio; Horta, Bernardo; Lima-Costa, Maria; Pereira, Alexandre; LLerena, Adrián; et al.
Abstract We present allele frequencies involving 39 pharmacogenetic biomarkers studied in Brazil, and their distribution on self-reported race/color categories that: (1) involve a mix of perceptions about ancestry, morphological traits, and cultural/identity issues, being social constructs pervasively used in Brazilian society and medical studies; (2) are associated with disparities in access to health services, as well as in their representation in genetic studies, and (3), as we report here, explain a larger portion of the variance of pharmaco-allele frequencies than geography. We integrated a systematic review of studies on healthy volunteers (years 1968–2017) and the analysis of allele frequencies on three population-based cohorts from northeast, southeast, and south, the most populated regions of Brazil. Cross-validation of results from these both approaches suggest that, despite methodological heterogeneity of the 120 studies conducted on 51, 747 healthy volunteers, allele frequencies estimates from systematic review are reliable. We report differences in allele frequencies between color categories that persist despite the homogenizing effect of >500 years of admixture. Among clinically relevant variants:CYP2C9*2 (null), CYP3A5*3 (defective), SLCO1B1-rs4149056(C), andVKORC1-rs9923231(A) are more frequent in Whites than in Blacks. Brazilian Native Americans show lower frequencies ofCYP2C9*2, CYP2C19*17 (increased activity), and higher ofSLCO1B1-rs4149056(C) than other Brazilian populations. We present the most current and informative database of pharmaco-allele frequencies in Brazilian healthy volunteers.